From Port Arthur to the Lindt cafe siege: The role of digital publics in challenging Australian print media agenda setting practices - Son, Catherine Jane (AoIR Selected Papers of Internet Research, 2017)
Technological advances such as the internet and smart phones have fundamentally altered the media landscape since Australia’s worst mass shooting at Port Arthur in 1996. Today, with the emergence of smart phones, social media, eyewitness contributions to news websites and audience measurement tools, digital publics have greater opportunities to contribute to the news agenda than ever before. Using a combination of content and discourse analyses, as well as oral history interviews with Australian journalists, this research explores whether advances in communication technology have achieved early hopes that digital publics would challenge established media agenda setting practices in Australia. To assess the evolution of agenda setting by the Australian print media over the past two decades, the object and attribute salience featured in print media reports of two events of national significance – the Port Arthur massacre in 1996 and Lindt café siege in 2014, are analysed. Interviews with journalists who reported either or both events provide crucial insight into whether journalists’ self-perceptions of the challenges digital publics present to their agenda setting role is reflected in the agenda contained in reports of these two incidents. This research contends that, despite increased opportunities for audience participation over the past two decades, and journalists’ assertions to the contrary, advances in communication technology since Port Arthur have failed to realise initial expectations of presenting a significant challenge to established print media agenda setting practices in Australia.